Koordinasi Administratif Lintas Unit : Menjaga Alur Kerja dalam Struktur Organsasi Bertingkat di PT. Swabina Gatra - Nathalie Aurelia Simangunsong; Tri Kartika Pertiwi (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This writing aims to revisit the results of a community service activity by analyzing how cross-unit administrative coordination is implemented to maintain workflow within the tiered organizational structure at PT. Swabina Gatra. The focus of the research is directed at the effectiveness of inter-unit coordination processes, particularly in managing incoming and outgoing mail, distributing internal documents, and using the ERP system for administrative recapitulation. The method used is descriptive qualitative, with data collection techniques including direct observation and documentation during the Merdeka Belajar Kampus Merdeka (MBKM) internship program. The findings show that cross-unit coordination has been carried out systematically, involving several stages of verification and information distribution. However, challenges were still found, such as delays in data collection from other units, suboptimal implementation of comprehensive administrative system digitalization, and reliance on informal communication. Therefore, strengthening coordination can be achieved through the development of cross-unit SOPs, digital system integration, and enhancement of human resource capacity to create a more efficient and accountable workflow.